The use of Bally-Valens-Rehab shoes to improve gait in patients following stroke - Jan Kool; P. Oesch; U. Sloksnath; O. Knusel (AOSIS, 1999)
A randomised study was conducted to determine the influence which the Bally-Valens-Rehab shoes may have on gait in patients following stroke. The 11 subjects were all independent ambulators who were more than one year post stroke. Measurements were performed twice in opposite order to balance order effects. The reliability of the measurements was good (r>0.97). With the Bally-Valens-Rehab shoes, velocity improved by 8,6% from an average of 0.59 to an average of 0,64 m/s (p=0.021). Step-length gained 6,2% (42,1 cm to 44,5 cm, p=0.026) and endurance improved from 119 to 126 m/3 minutes (p=0.016). Meanwhile, ground reaction forces revealed a decrease in lateral force indicating a narrower, more normal gait (p=0.059). The anterior-posterior force increased significantly (p=0.021) showing that the shoes enhance heel-rise. The measurements confirmed the subjective findings and showed that use of the Bally-Valens-Rehab shoes in stroke patients may improve gait and enhance rehabilitation.